ANALISIS INTERAKSI PENGUNJUNG KAFE TUGU LIMAU - Abdul Aziz; Rustiyarso Rustiyarso; Izhar Salim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis research has the purpose to understand the social interaction among the customers of Tugu Limau Cafe in Dusun Mawar of Mekar Sekuntum village. The method used in this research is descriptive type of qualitative research. The source of the research data is the customers Tugu Limau Cafe. In collecting data, the method used are through observations, interviews, and documentation, while tools used in collecting data are observation and interview guidelines, notes and archives. The analysis in the research is presented in qualitative descriptive of four reliable information sources consist of customers and servants of the cafe. The outcome of this research shows that interaction among the customers of the café in the form of social contact and communication is going on very well, the café customers make primary social contact through face to face encounters, smiling towards each other’s, handshaking and hugging. There is also secondary social contact in the use of smartphones as the means of communication. The communication among the customers is going on well, which is proven by fact that the customers use verbal communication using the same language which is Bahasa Melayu Sambas, therefore the communication goes on fluently as both sides able to understand each other very well. Keywords: Cafe Customers, Social Interactions